MANAGEMENT OF ANESTRUS AND SUBESTRUS COWS USING HORMONALANDNON~ORMONALDRUGS. - KUMAR, RAJESH; BUTANI, M G; DHAMI, A J; KAVANI, F S; SHAH, R J; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2011)
A total of 57 anestrus/subestrus crossbred cows were divide._{in to three treatment groups, each of 13, 13and 23 cows, keeping 8 cows as untreated control. Thirteen true anestrus cows were treated with nutritionalsupplements for 15 days and another 13 with single dose of GnRH 20 μg i/m, while 23 subestrus cows weretreated with single dose of PGF 2a 500 μg i/m. Animals detectti"d irf~strus were inseminated artificially. The estrusinduction response for the 3 groups was 76.92, 84.62 and 91 .30 %, with the mean interval of 26. 70±4.52, 28.27±6.46and 3.52±0.46 days (P
Keywords: Anestrus; Cows; Hormonal/Non-hormonal therapy; Estrus induction; Conception